A portrait is for not being alone - Tomsich, Francisco (knjige, 2025)
This booklet serves as a handbook for educators interested in applying strategies derived from contemporary portrait practices to their own work. It is based on the pedagogical model of actuation A Portrait Is for Not Being Alone, developed over many years by visual artist, cultural worker, and art teacher Francisco Tomsich. This model has been implemented through workshops, series of workshops, and exhibitions conducted in various contexts, countries, and languages, involving participants of diverse ages, backgrounds, and educational levels—often mixed.
Keywords: delavnice; Portreti; portretiranje; Priročniki; priročniki za učitelje; risanje